Primary elements of the indigenous peoples’ right to self-determination and their reflection in international cases - M. Yu. Zadorin; E. F. Gladun (Правоприменение, 2022)
The article touches upon the issues of law enforcement and court practice related to the collective rights of aboriginal communities.The purpose of the article is to reveal the content of the right to self-determination through the prism of the most significant cases related to indigenous peoples.The methodological basis of research is the general principles of scientific knowledge, widely used in works in the field of law: system-structural, formal-legal, comparative-legal, historical, methods of analysis and synthesis, analogies, etc. Particular attention was paid to the formal legal method, which was used by the authors of the study to analyze international judicial practice on the rights of indigenous peoples, as well as, in some cases, the national legislation of the countries participating in a particular case.The main results, scope of application. The right to self-determination of indigenous peoples is multicomponent and includes a number of specific elements and facets of interpretation. The authors have made an attempt to reveal the fundamental elements of the right to self-determination of indigenous peoples, which, in their opinion, consist of: the right to sovereignty as such, or autonomy and recognition as collective subjects of law, the right to land and resources, traditional nature management, autonomous education, mothertongue and culture.For each of the above-mentioned elements, a specific case is described, which was considered in international courts, primarily in the International Court of Justice, the Inter-American Court of Human Rights, the ECHR and etc.Conclusions. International recognition of a state through inclusion in the UN General Assembly is impossible without the permission of the Security Council; the issue of “effective occupation” has played and continues to play a large role in the issue of governance and sovereignty over a specific space and territory, and not only settlers, but also traditionally living indigenous peoples play a significant role;Indigenous peoples living in the coastal zone should have the right to dispose of income from the exploitation of the continental shelf; the relationship with the land is not only a matter of ownership and production, but a material and spiritual element that indigenous peoples must fully enjoy, if only to preserve their cultural heritage and pass it on to future generations; the status of “national minority” deprives the indigenous people of priority in the use of land for traditional reindeer herding; means of ensuring freedom of expression of indigenous peoples is an important element for the promotion of identity, language, culture, self-identification, collective rights.